(untitled) (ABDIMAS: Jurnal Pengabdian Masyarakat, 2025)
Stress and anxiety issues among students in the Indonesia–Malaysia border region pose a serious challenge to the learning process. The inability to manage emotions can interfere with students’ concentration and academic development. This community service activity aims to improve teachers’ competence in managing stress and anxiety through integrative counseling based on Mindfulness-Based Stress Reduction (MBSR) and muhasabah, with the hope that teachers will be able to apply these techniques both for themselves and to assist their students. The participants were 25 teachers from partner schools in the border region. The workshop was conducted face-to-face through theory and practice sessions, supplemented by group discussions. To assess the impact of the activity, participants filled out instruments before and after the training and wrote reflections. The results showed an increase in teachers’ understanding, with 65% in the high category, 25% in the medium category, and 10% in the low category. Although an increase in teacher competence was evident, the limitation of this activity was the lack of long-term data on direct application to students and the sustainability of the practice in schools. Therefore, follow-up through continuous mentoring is necessary so that the benefits of this program can be felt more widely.